O olhar ampliado de Gerd Bornheim na crítica de arte - Santos, André Silva dos (Revista do Colóquio, 2023)
Gerd Bornheim's experience in the field of art criticism becomes a curious fact, as the author dedicated himself to writing essays and even book chapters on the subject, therefore, art criticism will be the starting point for us to understand his biography and, for that, we underline some pertinent points that characterize the life and work of this important Brazilian philosopher, who transited between the 20th and 21st centuries. This is a qualitative and bibliographic study of a historical-artistic and philosophical nature, which proposes to cover the interpretation of subjective questions related to the Brazilian philosopher. Gerd Bornheim left a rich and diverse theoretical arsenal that transits through philosophy and art. Many of his bibliographic productions deal with theatrical art in dialogue with theorists who are icons of this universal artistic language, such as Bertolt Brecht.Keywords: Gerd Bornheim; Art criticism; Theater; Language.